The Application Status of Nanoscale Cellulose-Based Hydrogels in Tissue Engineering and Regenerative Biomedicine - Wang, Chenyang; Bai, Jin; Tian, Pei; Xie, Rui; Duan, Zifan; Lv, Qinqin; Tao, Yuqiang (Frontiers in Bioengineering and Biotechnology, 2021)
As a renewable, biodegradable, and non-toxic material with moderate mechanical and thermal properties, nanocellulose-based hydrogels are receiving immense consideration for various biomedical applications. With the unique properties of excellent skeletal structure (hydrophilic functional groups) and micro-nano size (small size effect), nanocellulose can maintain the three-dimensional structure of the hydrogel to a large extent, providing mechanical strength while ensuring the moisture content. Owing to its unique features, nanocellulose-based hydrogels have made excellent progress in research and development on tissue engineering, drug carriers, wound dressings, development of synthetic organs, 3D printing, and biosensing. This review provides an overview of the synthesis of different types of nanocellulose, including cellulose nanocrystals, cellulose nanofibers, and bacterial nanocellulose, and describes their unique features. It further provides an updated knowledge of the development of nanocellulose-based functional biomaterials for various biomedical applications. Finally, it discusses the future perspective of nanocellulose-based research for its advanced biomedical applications.